Polin : Focusing on Aspects and Experiences of Religion. - Polonsky, Antony (Polin Studies in Polish Jewry Ser., 1998)
Addressing various aspects of Jewish life and religion, particularly in the last two centuries, this book examines different aspects of the Hasidic tradition; present-day contacts between Bobower Hasidism in New York and Bobowa in Poland; and how a rabbi trained in the Lithuanian tradition adapted to the very different conditions of the United States. The modifications of Jewish religious tradition practiced in the modern pre-war synagogues in Warsaw, L dz, and Lw w are considered, as is the attempt by Hillel Zeitlyn to re-interpret Jewish tradition in the interwar years.